Didactic Sequences as a potential instrument of the reflective formation of teachers - Gonçalves, Adair Vieira (2016)
This paper aims not only to report the continuing education of ElementarySchool teachers which comprises the fi rst stage of the development of astrictu sensu research project (Masters in Languages), but also to presenttwo didactic sequences addressed to the teaching of text production inboth genres, the article of opinion and news. The planning of the materialhappened during the mediation process of two collaborating teachersinvolved with the research which in turn was grounded on the theoreticaland methodological contributions of sociodiscursive interactionism(regarding the construction of models and didactic sequences) and onthe action-research paradigms and collaborative work. In the investigatedcontext, interventional collaborative research is understood as an effectivemethodology for bringing the research products developed at the Universityinto the schools.